The Perception on Indonesia Policies to Overcome the Impact of Corona Virus Outbreak - Lita Kusumasari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
The Corona Virus led to global economy crisis, including in Indonesia. WHO also warn to all countries must strike a fine balance between protecting health, minimizing economic and social disruption, and respecting human rights. Based on the situation to amid Corona Virus outbreak, Indonesian Government added Rp405.1 trillion to national budget in 2020 for Corona virus. It is allocated to Rp75 trillion for health sector, Rp110 trillion for social welfare, Rp70.1 trillion for tax incentive and micro credit, and Rp150 trillion for Indonesia economy recovery including credit restructure and funding for micro, small, and medium enterprises. Indonesia government is trying to channeling the Corona virus outbreak to be controllable. The purpose of research study is examining Indonesian people perception toward strategy of Indonesian government. Prior researches stated that the impact of Covid-19 pandemic affects the economy in Indonesia, could harmed the economy, could cause liquidity problems and finally would get domino effect on the economy. Previous researches found based on the qualitative methods. This research approach used survey by electronic forms and quantitative methods approach used multiple regression. The result found that Indonesian people perception on health, social welfare net and fiscal strategy by Indonesian government was significantly contributed to economic goals in Indonesia toward Corona Virus Outbreak. This study in line with the claim of Indonesia government that the strategy is success.